KAITAN PELATIHAN DALAM UPAYA MENINGKATKAN KUALITAS KERJA KARYAWAN PT BOGOR AGRO LESTARI TAHUN 2007 - Dedy Mulyadi; Kartika . (Jurnal Ilmiah Binaniaga, 2007)
Considering the major role of human resource in achieving the company’s goal the company should provide an operational skill or knowledge directly from manager to employee’s levels. The company should give the employees a better understanding that the training is provided not only to execute the pre-determined program smoothly, but also to increase the quality of their achievement in their own field that in turn will influence their income, performance and future career planning. Comparing the statistical scores gained by the employee before and after the training proves the significant difference. After the training the score was higher (3.87%) than before the training (3.08%), which means that the training gave good impact. Other statistical computation using t – paired samples with α = 0.005 and degree of freedom (df = 29) also proved the difference where t counted (-38.445) is bigger than t table (-1.669). The training was basically aiming at formulating the expected ability from the employees to change their behavior. Such a change was formulated in terms of behavioral change and a short-term educational program by using systemic and organized procedures, so that operative employees learn technical and skill knowledge for specific purpose.